Evaluasi Pengelolaan Limbah Bahan Berbahaya dan Beracun oleh PT B di Bandara Internasional S - Tsania Putri Fadhila; Mila Dirgawati (Jurnal Serambi Engineering, 2024)
PT B is a company engaged in the business of airport-related services in Indonesia. There are 8 types of hazardous waste generated from S International Airport facilities, including used batteries, oil drums, oil cans, jerry cans, used oil, TL lamps, cloth, and medical cloth. The purpose of this research is to identify the types and sources of hazardous waste, determine the technical and non-technical aspects related to waste management, evaluate the suitability of hazardous waste management, and provide recommendations and suggestions in accordance with regulations related to hazardous waste. The research method used is a combination of the checklist method and the scoring method using a Guttman scale. The results showed that PT B received a score of 73,1 which was categorized as “Good”. Recommendations and suggestions that can be made by PT B to improve the suitability score are to carry out every hazardous waste management activity by referring to the regulations, and to strictly supervise the waste management that has been carries out so that it is always in accordance with the regulations related to hazardous waste management that apply in Indonesia.